2010
DOI: 10.1097/mph.0b013e3181d869d5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety, and Stress Comorbidities in Sickle Cell Anemia Patients With Vaso-occlusive Crisis

Abstract: We investigated the association of sickle cell anemia (SCA) vaso-occlusive crisis (VOC) with depression, anxiety, and stress disorders among Bahraini patients and controls. This was a cross-sectional study that involved administering Depression Anxiety Stress Scales (DASS-21) consisting of structured depression, anxiety, and stress scales to SCA patients with (n=138) and without (n=105) VOC. Multinomial regression and correlation analysis were used in assessing the association of VOC with depression and/or anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…16,17,18 Age is associated with greater severity of sickle cell disease, and the greater severity of SCD requires greater attention from parents. 19,20 Thus, it may represent a greater impact on the family's QoL. 20 The severity of SCD may place additional pressure on the caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,18 Age is associated with greater severity of sickle cell disease, and the greater severity of SCD requires greater attention from parents. 19,20 Thus, it may represent a greater impact on the family's QoL. 20 The severity of SCD may place additional pressure on the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Thus, it may represent a greater impact on the family's QoL. 20 The severity of SCD may place additional pressure on the caregiver. A study conducted in Brazil evaluated the burden and QoL of 37 caregivers of patients with sickle cell anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In managing serious and unpredictable complications, patients with SCD suffer numerous psychosocial problems such as reduced self-esteem, feelings of frustration (7), depression (7)(8)(9), anxiety and stress (8), and disruption of interpersonal relationships (10); these often lead to fatigue (11)(12)(13)(14) and poor quality of life (13,(15)(16)(17) in these patients. Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…These patients require repeated visits to the emergency and hospital for medical care (6,7). Therefore, SCD significantly affects the performance status (6) and quality of life in all dimensions (8) and can lead to reduced self-confidence, feelings of frustration, depression, anxiety, and stress (9,10). In addition, the pain leads to high consumption of narcotic drugs (11), which are the most used treatments for these patients (12).…”
Section: Sickle Cell Diseasementioning
confidence: 99%